Stress and Resilience of Japanese Teachers in Special Needs Schools for Students With Intellectual Disabilities During the COVID-19 Pandemic - Ogawa, Shuhei; Kawamura, Risato; Kojima, Michio (Frontiers in Education, 2022)
In Japan, numerous special needs school teachers take sick leave because of mental illness. This study aims to develop a stressor scale for special needs school teachers working during COVID-19 pandemic and to clarify the actual conditions and relationships among stressors, stress responses, and resilience of such teachers in schools for people with intellectual disability. The questionnaire was completed by 227 special needs teachers. Six factors emerged from factor analysis: difficulty in dealing with guardians, disconnection between schools and national and local educational policies, relationship difficulties among coworkers, busyness, lack of specialty, and trouble in dealing with COVID-19. The scale’s criterion-related validity and internal consistency were verified. The results revealed virtually no relationship between trouble in dealing with COVID-19 and stress responses. However, the higher the degree of relationship difficulties among coworkers and busyness, the higher their stress responses. Multiple regression analysis revealed that the resilience subfactors were negatively related to stress responses.